Mutations in ATP6AP2 cause autophagic liver disease in humans. Issue 6 (3rd June 2018) - Cannata Serio, Magda; Rujano, Maria A.; Simons, Matias
ABSTRACT: The biogenesis of the proton pump V-ATPase commences with the assembly of the proton pore sector V0 in the endoplasmic reticulum (ER). This process occurs under the control of a group of assembly factors whose mutations have recently been shown to cause glycosylation disorders with overlapping phenotypes in humans. Using whole exome sequencing, we demonstrate that mutations of the accessory V-ATPase subunit ATP6AP2 cause a similar disease characterized by hepatosteatosis, lipid abnormalities, immunodeficiency and cognitive impairment. ATP6AP2 interacts with members of the V0 assembly complex, and its ER localization is crucial for V-ATPase activity. Moreover, ATP6AP2 mutations can cause developmental defects and steatotic phenotypes when introduced into Drosophila. Altogether, our data suggest that these phenotypes are the result of a pathogenetic cascade that includes impaired V-ATPase assembly, defective lysosomal acidification, reduced MTOR signaling and autophagic misregulation.